PENGELOLAAN E- LAYANAN KONSELING DALAM PENINGKATAN DISIPLIN PESERTA DIDIK BERBASIS WHATSAPP - Fatimah Ibda Fatimah Ibda; Inna Maiza Inna Maiza (Jurnal Ikhtibar Nusantara, 2024)
Counseling services are less effective in conveying relevant and useful information to students, as well as the use of media is not optimal and there is a lack of time in providing counseling services to improve student discipline. Electronic counseling is an alternative that is relevant to technological developments and the needs of today's modern students. However, it is necessary to manage WhatsApp-based e-counseling services to improve student discipline at SMAN 4 Banda Aceh. The aim of this research is to determine the planning, implementation and obstacles to WhatsApp-based e-counseling services in improving student discipline. This research uses a descriptive qualitative approach. The research subjects were guidance and counseling teachers, homeroom teachers, and students. Data collection techniques use observation, interviews and documentation, then the data is analyzed through triangulation techniques. The results of this research show that planning WhatsApp-based e-counseling services was carried out through stages: 1) survey of student needs and interests; 2) communication with parents and homeroom teachers 3) formation of several Whatsapp groups; 4) distribution of tasks to guidance and counseling teachers; 5) and long term planning. The implementation of WhatsApp-based e-counseling services is carried out in stages: 1) Analysis of student needs via the assessment questionnaire link; 2) introduction of WhatsApp-based counseling materials to parents and students; 3) individual counseling and group counseling via WhatsApp; 4) follow-up to students who have not changed; 5) collaboration with parents and homeroom teachers to resolve cases. Obstacles in managing WhatsApp-based e-counseling services include: 1) students are late in filling out assessment questionnaires via the website; 2) misuse of WhatsApp; 3) technological limitations; 4) lack of non-verbal communication between counselors and students